Characteristics of the Health-Related Physical Fitness Questionnaire: Serbian version - Velimir Miličković; Željko Krneta (Exercise and Quality of Life)
Modern directions in the development of physical education in the world emphasize the importance of health-related physical fitness (HRPF), with special attention to the development and monitoring of knowledge about HRPF through the application of a targeted questionnaire. The main goal of this research was to analyze the characteristics of the HRPF questionnaire adapted to the Serbian language. After adjustment to Serbian language and terminology, questionnaire was administered to a sample of 270 children, 175 children of the fifth grade (11 to 12 years) and 95 children f the eighth grade (14 to15 years). In both subsamples, the questionnaire has shown good internal consistency (Cronbach's α was 0.73 for fifth grade and 0.67 for eighth grade) and good features of most questions. The results also suggested problems with three questions which needed adjustment for further use: Question Q2 - Jana wants to do something after school what would help her to become successful in the football team she plays in, she should; Question Q11 - Volleyball is good; Question Q25 - If you want to be stronger, you should. After that kind of implementation, the questionnaire can be recommended for evaluation of HRPF of older primary-school children.